1996
DOI: 10.1097/00000539-199607000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Ondansetron and Droperidol in the Prophylaxis of Postoperative Nausea and Vomiting

Abstract: The aim of this study was to compare the efficacy and safety of ondansetron plus droperidol with each drug alone or placebo in the prevention of postoperative nausea and vomiting (PONV). One hundred females, aged 18-65 yr, ASA physical status I-II, undergoing general anesthesia for elective abdominal surgery were included in a prospective, double-blind, placebo-controlled, randomized study. A standardized anesthetic technique and postoperative analgesia (ketorolac plus patient-controlled analgesia [PCA] with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…Ondansetron and droperidol may thus be less effective prophylactic agents in breast surgery than in gynaecological and abdominal surgery. However, the incidence of PONV still remained high in some of the studies referred to, varying between 37% and 72% after ondansetron 4-8 mg and 24% and 83% after droperidol 1.25-2.5 mg were administered; these figures are in accordance with our results [13][14][15]18].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ondansetron and droperidol may thus be less effective prophylactic agents in breast surgery than in gynaecological and abdominal surgery. However, the incidence of PONV still remained high in some of the studies referred to, varying between 37% and 72% after ondansetron 4-8 mg and 24% and 83% after droperidol 1.25-2.5 mg were administered; these figures are in accordance with our results [13][14][15]18].…”
Section: Discussionsupporting
confidence: 92%
“…Prospective studies of a combination of antiemetic drugs, such as ondansetron and droperidol, appear to be of interest, because various antiemetic drugs have different receptors and sites of action; improved results can therefore be expected [15]. Another method of reducing PONV in breast surgery may be the use of propofol to induce and maintain anaesthesia [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous droperidol administered at the end of anesthesia has been shown to compare favorably with the newer but more expensive 5-HT3 receptor antagonists (2). Several studies have also indicated, however, that combination regimens will prevent postoperative nausea and vomiting more effectively than either droperidol or 5-HT3 receptor antagonists as monotherapy (12). This synergism is attributed to activation of additional emesis-related receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Data did not show better outcomes with multiple-drug regimens, in contrast to previous studies in the literature. [36][37][38][39][40][41] A recent meta-analysis of 17 randomized, controlled trials involving 1946 ambulatory and inpatient surgery patients was performed to define the antiemetic efficacy and safety of dexamethasone in prevention of PONV. 36 Prophylactic dexamethasone was effective in reducing PONV without clinically relevant toxicity in otherwise healthy patients.…”
Section: Patient Satisfaction With Prophylaxis For Ponv Darkow Et Almentioning
confidence: 99%